(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Creativity is one of the most important aspects of human life. Creativity can help someone in problem solving and facing the development of science and technology. The creativity of students will develop optimally if the teacher has competence that is qualified. The more creative a teacher, the more creative students. This research aims to get a description of the creativity capability of the 5th graders in elementary schools in Gorontalo Province. The research was conducted in 5yearselementary school graders in Gorontalo Province. The research method is descriptive-quantitative with population samples from 6 districts of Gorontalo Province. The sample was taken using the stratified random sampling technique for each district, so 120 students were obtained. The instrument used the Verbal Creativity Test was developed by Munandar and analyzed data using descriptive statistics. The result shows that about 75 % of the 5th graders in elementary school in Gorontalo Province have a low level of creativity ability. This show that the low creativity of students is due to the absence of variation in providing methods and strategies of learning by teachers.